Directory of European Polar Research Funding Programmes (EU-PolarNet 2, 2022)
The polar regions are sentinels of climate change and human resilience and they are also a proven bastion for international cooperation in research and nature protection. European researchers have made significant contributions to understand the consequences of climate change and the structure and functioning of ecosystems at both polar regions, and their global interconnections. Unifying, disseminating and coordinating all European research actions is one of the tasks of the EU-PolarNet 2 project. EU-PolarNet 2 – “Coordinating and co-designing the European Polar Research Area” is a coordination and support action funded by the European Commission in Horizon 2020. It comprises 25 partners representing all European and associated countries with well-developed Polar research programmes and activities. EU-PolarNet 2 aims to provide a platform to co-develop strategies to advance European polar research and its contribution to policy-making processes. By involving all relevant stake- and rightsholders it supports the development of transdisciplinary and transnational polar research actions of high societal relevance. To ensure that such an important platform is sustained after the four years of project duration, the project works with funding agencies, national polar research institutes, operators of national polar programmes, polar experts and the European polar research community to discuss and implement the identified research actions. The final goal of EU-PolarNet 2 is to create a permanent European Polar Coordination Office which will continue the work of EU-PolarNet 2 in a sustained way